A Comparative Analysis Of The Regional Development Agencies In Europe And Turkey - SavaÅŸ-YavuzÃ§ehre, PÄ±nar (European Scientific Journal, ESJ, 2016)
The Regional Development Agencies were put into effect in Turkey within 26 agencies with the Law number 5449 that was passed in 2006 after European countries as a foundation highlighting the understanding of territorialisation, localization and competition. The aim of the study is to compare the recently founded Development Agencies in Turkey with the long-established system in Europe. Moreover in this study, the concepts of region and regional development are described and the origination conditions of development agencies in Turkey and in the world are explained shortly. The structure of the development agencies in European countries, especially in those in the European Union (EU), which have been active for a long time, is compared with that of the development agencies in Turkey from many perspectives. This study reveals that the development agencies in Turkey and Europe show differences in terms of their aims, legal positions, and supervisions, whereas, they show similarities in terms of their founders, general characteristics, organizational structures, fields of activities, staff employment, financial sources and project centers.